Agglomeration without Growth? A Comprehensive Assessment towards Palembang’s Industrial Agglomeration Policies - Muhammad Raka Hadiyan; Andi Rahmansyah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2025)
This study undertakes a comprehensive assessment of Palembang’s industrial agglomeration performance while also map policy interventions required to strengthen future outcomes. Using a mixed-method approach, we construct a five-dimensional Industrial Agglomeration Index: Capital Access (CAP), Infrastructure (INF), Local Market Conditions (LOM), Labor Availability (LAB), and Living Quality (HDI), to later examine its relationship with Palembang’s Balassa Index over 2015–2024. Despite Palembang’s poor performance when being compared nationwide, quantitative findings instead reveal a positive transformation within the city’s manufactures, with the Index rising from -0.133 to 0.609 under a 10-year observation span. However, when being deepened from each dimension, progress remains uneven; LOM, INF, and LAB exhibit persistent volatility. Regression analysis uncovers a significant one-to two-year temporal lag between agglomeration conditions and realized industrial performance. Qualitative insights from stakeholder interviews identify three priority interventions: sustained infrastructure investment, local market development, and labor market stabilization. The findings demonstrate that effective agglomeration policy requires coordinated, multi-dimensional attention and a medium-term evaluation horizon to deliver inclusive growth. Those requirement becomes really urgent for a city like Palembang to increase their manufacturing power and achieve stable economic growth.